Social vulnerability and medication adherence in individuals with chronic obstructive pulmonary disease - Efil, Sevda; Bükrük, Ceren Mina; Özen, Ebru (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The association between social vulnerability and medication adherence in individuals with chronic obstructive pulmonary disease is unclear. The aim of this study was to show the correlation of social vulnerability and medication adherence in individuals with chronic obstructive pulmonary disease. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Data collection was conducted by face to face interview in November 2022 and May 2023. Social vulnerability and medication adherence were evaluated using the Social Vulnerability Scale and the Medication Adherence Report Scale respectively. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The mean scores of individuals with chronic obstructive pulmonary disease for social vulnerability and medication adherence were 20.02±6.69 and 22.76±3.29 respectively. Levels of social vulnerability varied according to comorbidity, hypertension, heart failure, visit to emergency service in the last three months due to COPD exacerbation, and using herbal products instead of medication (p<0.05). Mean scores for medication adherence were lower in women, never smokers, and those who used herbal products instead of medication (p<0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Having a higher level of social vulnerability is associated with worse medication adherence (r=-0.31, p<0.01). Individuals using herbal products are found to be at risk for social vulnerability and non-adherence to medication (p<0.05).